2013
DOI: 10.1002/ajmg.a.35969
|View full text |Cite
|
Sign up to set email alerts
|

Deletion 16p13.11 uncovers NDE1 mutations on the non‐deleted homolog and extends the spectrum of severe microcephaly to include fetal brain disruption

Abstract: Deletions of 16p13.11 have been associated with a variety of phenotypes, and have also been found in normal individuals. We report on two unrelated patients with severe microcephaly, agenesis of the corpus callosum, scalp rugae, and a fetal brain disruption (FBD)-like phenotype with inherited deletions of 16p13.11. The first patient was subsequently found on whole exome sequencing to have a nonsense mutation (p.R44X) in NDE1 on the non-deleted chromosome 16 homolog. We then undertook copy number studies of 16p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 27 publications
(49 reference statements)
1
79
0
Order By: Relevance
“…However given that incomplete penetrance and a potential 2-hit hypothesis of inheritance may contribute to neurodevelopmental phenotypes associated with CNVs of 16p13.11, it is plausible that the 16p13.11 duplication is contributing, at least partially, to the phenotype of Patient 4 (epilepsy with Lennox Gastaut syndrome). 11 In Patient 5, two CNVs were identified, one of which was a de novo 10q21.3 deletion containing CTNNA3, the gene encoding an important cell adhesion protein Catenin. This CNV has been identified in association with the LandauKleffner spectrum of epilepsy, 12 however none of the nine patients in Decipher with an overlapping CNV of 10q21.3 had epilepsy as part of their phenotype, so identifying likely candidate genes is not always possible.…”
Section: Discussionmentioning
confidence: 99%
“…However given that incomplete penetrance and a potential 2-hit hypothesis of inheritance may contribute to neurodevelopmental phenotypes associated with CNVs of 16p13.11, it is plausible that the 16p13.11 duplication is contributing, at least partially, to the phenotype of Patient 4 (epilepsy with Lennox Gastaut syndrome). 11 In Patient 5, two CNVs were identified, one of which was a de novo 10q21.3 deletion containing CTNNA3, the gene encoding an important cell adhesion protein Catenin. This CNV has been identified in association with the LandauKleffner spectrum of epilepsy, 12 however none of the nine patients in Decipher with an overlapping CNV of 10q21.3 had epilepsy as part of their phenotype, so identifying likely candidate genes is not always possible.…”
Section: Discussionmentioning
confidence: 99%
“…NDE1 deficiency impairs neurogenesis, by causing profound neuronal proliferation defects and a deficiency in cortical lamination, as observed in Nde1-null mice and in patients with NDE1 homozygous mutations, who present extreme microcephaly with lissencephaly 106 107. Severe microcephaly, including fetal brain disruption, can also be caused by the combination of a 16p13.11del and a mutation on the non-deleted NDE1 homologue 108. As the 16p13.11 region includes other genes expressed during brain development, such as ABCC1 , NOMO1 , NTAN1 , PDXDC1 , it has been suggested that sequencing these candidate genes for second-hit mutations in patients with 16p13.11del and severe neurodevelopmental phenotypes could give new insights into these disorders 108…”
Section: Recurrent Cnvs Associated With Increased Risk For Ndsmentioning
confidence: 99%
“…Subsequent work by many groups has to date identified 19 LIS-SBH associated genes including LIS1 , many of which are microtubule structural (tubulin) or microtubule-associated proteins (MAPs), including: ACTB, ACTG1, ARX, CDK5, CRADD, DCX, DYNC1H1, KIF2A, KIF5C, LIS1, NDE1, RELN, TUBA1A, TUBA8, TUBB, TUBB2B, TUBB3, TUBG1 , and VLDLR [Abdollahi et al, 2009; Boycott et al, 2009; Breuss et al, 2012; Di Donato et al, 2016a; Gleeson et al, 1998; Hong et al, 2000; Jaglin et al, 2009; Keays et al, 2007; Kitamura et al, 2002; Magen et al, 2015; Poirier et al, 2013a; Poirier et al, 2010; Reiner et al, 1993; Riviere et al, 2012; Willemsen et al, 2012]. We include NDE1 , as the associated gyral malformation resembles tubulinopathy-associated dysgyria [Paciorkowski, 2013 PMID 23704059]. An abnormal gyral pattern has also been described with mutations of RNU4ATAC , but too few brain images have been published to allow us to define the malformation [Abdel-Salam et al, 2013].…”
Section: Introductionmentioning
confidence: 99%